PENDIDIKAN ANTI KORUPSI DALAM AL-QURAN (Perskripsi Moral-Religius dalam Memerangi Praktik Rasuah) - Irham; Haq, Sansan Ziaul (Program Studi Pendidikan Agama Islam, Fakultas Agama Islam UNISMA Bekasi, 2024)
This study seeks to integrate anti-corruption education with an Islamic perspective. This study uses a thematic-analytical method whose primary source is the Quran, interpreted from various commentaries. The findings show that, in substance, the Qur'an has taught us not to commit corruption. Phrases found in the Qur'an whose meaning is commensurate with corruption are 'eating other people's property unlawfully' (akl amwal al-nas bi-al-batil), 'eating illegally' (akl al-suht), and bribing judges (al-idla' ila-al-hukkam). This study further shows that corruption falls into the category of unlawful taking away other people's rights, while bribery is one of the doors to this unjust act. Therefore, corruption is a grave sin that will have serious consequences hereafter. The findings of this study can further contribute to the development of anti-corruption education from an Islamic perspective.